Conducts of immediate puerperals in front of a suspended gagging in babies (Research, Society and Development, 2021)
Airway obstruction caused by choking is a serious and potentially fatal accident that is very common among infants and children in their first years of life, but it can occur in any age group. The aim of this study is to investigate the behavior of postpartum women admitted to a teaching hospital when faced with supposed choking in babies. The sample consisted of immediate postpartum women admitted to the maternity ward of a public teaching hospital. Quantitative and qualitative data on sociodemographic, health and knowledge about choking in infants were collected. Sixty-one women participated, most of them single, with high school education and a family income of up to two minimum wages. Regarding the training on the degassing maneuver, 85.2% had never done it and 95.1% considered it important. Three themes were extracted from qualitative information: autonomy of health care, transfer of health care and disability, which gave rise to six central ideas. It is concluded that there is an important deficit of knowledge and assertive behavior among postpartum women on the subject, which reinforces the importance of investment by hospital teams in the training of mothers and their families in planning for discharge.